School Financial Management For Poor Families (A Site Study at SD N Batursari 6 Mranggen Demak) - Sutinah, Sutinah (2011)
The objectives of the research are (1) to describe the characteristics of school financial management to students of poor families at SD N Batursari 6 Mranggen Demak, (2) to describe the financial accountability of school funds to students of poor families at SD N Batursari 6 Mranggen Demak. This is a qualitative research with an ethnography design that conducted at SD N Batursari 6 Mranggen Demak. Human resource in this reserach are Principal, Treasurer, and School Board at SD N Batursari 6 Mranggen Demak. Data collection techniques in this research used are observation, interview and documentation. Technique of data analysis conducted with data collection, data reduction, data display, and conclusion. Data validity test use triangulation. The results of this research are (1) School financial management process begins with the formation of a small team consisting of principal, treasurer, and school board. Small team assigned to assess and select students from poor families who will receive financial aid of the school. (2) The school financial accountability process contains about things related to the statistics of beneficiaries, distribution, absorption and utilization of funds, results of evaluations monitoring and complaint issues. School financial accountability process conducted every three months. The report also posted on the bulletin board in the school.